Assisted Reproductive Technology in China: Results Generated From Data Reporting System by CSRM From 2013 to 2016 - Hu, Linli; Bu, Zhiqin; Huang, Guoning; Sun, Haixiang; Deng, Chengyan; Sun, Yingpu (Frontiers in Endocrinology, 2020)
Background: What are the trends and figures in the treatments involving Assisted Reproductive Technology (ART) in mainland China? Method: The Chinese Society of Reproductive Medicine (CSRM) retrospectively collected and analyzed data from 2013 to 2016 in 28 province of China by CSRM ART Data Reporting System. Results: Among the 327 centers in China by December 2016, 133 centers reported 1 211 303 cycles and 470 725 infants in the four year period. Since 2013, the total number of frozen embryo transfer (FET) cycles, PGD/PGS cycle showed an increasing trend year by year. However, the number of donor sperm (DS) and donor egg (DE) cycles remained at a low level. Pregnancy outcomes such as implantation rate, pregnancy rate and delivery rate per embryo transfer cycles were stable in all types of ART, but decreased dramatically with increasing age. However, the average number of transferred embryos gradually decreased from 2013 to 2016, especially in PGD/PGS cycles. Thus, multiple pregnancy rate also decreased, it decreased significantly in PGD/PGS cycles from 30.5% in 2013 to only 1.7% in 2016. Conclusions: The current study gives valuable information for both physicians and patients to know better about the outcome, as well as for administrators for policy development.